2021
DOI: 10.3389/fpubh.2020.604702
|View full text |Cite
|
Sign up to set email alerts
|

The Forbidden Reward. The Emergence of Parent-Child Conflicts About Food Over Time and the Influence of Parents' Communication Strategies and Feeding Practices

Abstract: One of the most critical arenas for conflicts between parents and their children relates to food. Although parent-child conflicts about food are a real occurrence, this form of parent-child interaction has been rarely examined. Given the special role of parents in shaping children's diet, we especially focus on the impact of parental measures. This study investigates how parental communication strategies (i.e., active vs. restrictive) and feeding practices (i.e., overt control vs. covert control) affect the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…A previous Dutch study, which did not differentiate between parents (father or mother), also found that parents of children from Dutch backgrounds reported the highest scores for control over eating [ 45 ]. In line with previous literature, our study found that mothers with a higher educational level reported more use of covert control [ 18 , 42 , 46 ]. To gain further insights into the relationship between economic differences and the use of parenting practices, it is recommended to repeat this study across diverse communities.…”
Section: Discussionsupporting
confidence: 92%
“…A previous Dutch study, which did not differentiate between parents (father or mother), also found that parents of children from Dutch backgrounds reported the highest scores for control over eating [ 45 ]. In line with previous literature, our study found that mothers with a higher educational level reported more use of covert control [ 18 , 42 , 46 ]. To gain further insights into the relationship between economic differences and the use of parenting practices, it is recommended to repeat this study across diverse communities.…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings from another study, parents who had less education used food as a reward slightly more frequently than parents who had more education (Jansen et al, 2020). Additionally, a study found that parents' use of unhealthy food as a reward triggered food conflicts with children (Spielvogel et al, 2020). On top of that, mothers with lower education levels may be more concerned about their children's weight status.…”
Section: Discussionmentioning
confidence: 98%
“…This study was part of a larger project; 49,50 in this section we report only variables relevant to our analysis.…”
Section: Methodsmentioning
confidence: 99%